Designing of Mikrokontroler E-Learning Course: Using Arduino and TinkerCad - Direstu Amalia; IGAAMOka IGAAMOka; Virma Septiani; M Rafli Fazal (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2020)
During the Covid-19 pandemic, education and training activities began to shift to online classes. The problem is, the training carried out is only limited to theory-based training, not practical training. The current situation raises new possibilities in changing the learning method to fully online classes, with the character of vocational education, namely student-centered learning. The expected advantage is that education can be applied anywhere, this article explains how education providers develop research and development with the ADDIE method to analyze curriculum and learning models by promoting project-based learning methods where students are expected to be able to develop actively in learning. The TRBU Study Program designed the Arduino IDE microcontroller online training using free TinkerCad simulation with asynchronous learning materials through the LMS and supported by online classes using the zoom application. The results showed that 42.9% of students have high interest in online workshop and 92.9% agree that this online course needs to be re-implemented.